2020
DOI: 10.1002/ptr.6908
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects and safety of Zuogui pill for treating osteoporosis: Current evidence for an ancient Chinese herbal formula

Abstract: The aim of this study is to systematically evaluate existing evidence of the Chinese herbal formula, Zuogui pill (ZGP), for the treatment of osteoporosis. A systematic literature search was performed in six electronic databases. The authors independently extracted data in pairs and evaluated the risk of bias. A total of 221 articles were identified initially, of which 12 relevant studies were enrolled. The primary outcome was fracture incidence and bone mineral density (BMD) at different sites. Bone metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…The findings of another systematic review and meta-analysis indicated that Liuwei Dihuang pill is effective in improving BMD of hip and lumbar spine and alleviating pain in patients with postmenopausal OP (Wang, et al, 2020a). Besides, the findings of a previous review showed that Zuogui pill combined with anti-OP drugs remarkably increased BMD at different sites and improved the bone metabolism markers for treating OP (Li, et al, 2020). Besides, most of our findings were congruent with the data of An et al (An, et al, 2019).…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…The findings of another systematic review and meta-analysis indicated that Liuwei Dihuang pill is effective in improving BMD of hip and lumbar spine and alleviating pain in patients with postmenopausal OP (Wang, et al, 2020a). Besides, the findings of a previous review showed that Zuogui pill combined with anti-OP drugs remarkably increased BMD at different sites and improved the bone metabolism markers for treating OP (Li, et al, 2020). Besides, most of our findings were congruent with the data of An et al (An, et al, 2019).…”
Section: Comparison With Previous Studiessupporting
confidence: 91%
“…It controls OP by regulating multiple signaling pathways and has the functions of increasing bone production, stabilizing bone structure, enhancing OB proliferation and differentiation, and inhibiting OC. In addition, Drynariae Rhizoma can increase the body’s absorption of calcium, promote calcium transport into bone, strengthen bone mineralization, maintain the balance of bone remodeling; regulate the metabolic level of the hypothalamic-pituitary-gonadal axis, improve endocrine function, inhibit the synthesis and secretion of inflammatory factors in bone metabolism, and have a potential anti-osteoporosis effect ( Zhao et al, 2020a ; Li J et al, 2021 ). Flavonoids are the main components of Drynariae Rhizoma in the prevention and treatment of OP.…”
Section: Kidney Tonifying Traditional Chinese Medicine In the Treatme...mentioning
confidence: 99%
“…Recently, Traditional Chinese medicine shows obvious curative effects on OP, which significantly increases bone density, reduces the incidence of fragility fractures, and plays anti-inflammatory and analgesic roles in OP patients (7)(8)(9). Especially, Bugu Shengsui Decoction (BGSSD), a traditional Chinese medicine compound formula, is applied to treat OP in clinical practice.…”
Section: Introductionmentioning
confidence: 99%